Partnership model in improving the welfare of corn farmers in Indonesia - Atmiko, Diyat; Riski, Faisal; Rispati, Nauru (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.49, 2022)
Indonesia is known as an agricultural country with the majority of its population working in the agricultural sector, but the welfare of farmers is still far from expectations. One of the ways to improve the welfare of farmers is through the concept of agribusiness partnerships. The pattern of cooperation in the form of agribusiness partnerships is very important as an alternative program to increase people's income. The writing method used a qualitative research which is a literature study by examining the partnership model in an effort to improve the welfare of corn farmers in Indonesia. The results of this study showed that the nucleus-plasma partnership model with private companies is widely applied in Indonesia. Focus on mutually beneficial and strengthening partnerships, providers of production facilities, technical guidance and marketing of products, as well as production of plasma smallholders by core companies with the aim of increasing income. The existence of a source of income and an increase in farmers' finances will have a positive correlation with increasing farmers' welfare.